Private Incentives to Innovate: Interplay of New Products and Brand-Name Reputation - Nina Leheyda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper studies the introduction of new products (increase in product variety) in the automobile industry. The focus is on the two sources of market power that may allow the firms to get higher profits (and, thus, recoup investments): new products and brand-name reputation. The effects of new products on the private incentives to innovate are investigated on the basis of the dataset for the German car industry for 2003. The dataset is rather unique in the sense that it contains detailed information on the technical characteristics of cars, prices and sales as well as information on the introduction of new car models (including new variants and versions) into the German car market at a very disaggregate level. It has been found that both a new model and brand-name reputation may allow the innovative firms to get some market power and recoup their investments. Competition is, however, not localized within a market segment and the class of new or old models, i.e., products from different market segments, new and old products compete with each other (coexisting and not eliminating each other) and do not constitute separate market niches. On the other hand, new (old) models are perceived to be closer substitutes than old (new) models. Consumer preferences towards brand and new products vary depending on their age.
Keywords: D43; L62; L13; 330; discrete choice models; automobile industry; new products; innovations; brandname reputation; Kraftfahrzeugindustrie; Innovation; Marktmacht; Produktimage; Diskrete Entscheidung; Wettbewerb; Ökonomischer Anreiz; Schätzung; Theorie; Deutschland